An Attempt to Understand the Negotiation of Teachers’ Identities in the Context of School Reform - Neira Del Ben, Paul (2019)
Political discourses that state that the quality of an educational system relies on the quality of its teachers are frequent nowadays. This approach remarks the importance of teacher’s identity. However, how many times is this issue actually taken into consideration by the educational reform processes? This question turns relevant when we realize that many of the reforms seek to penetrate the classroom, and the teachers’ own practices. The following essay is an exploration of the elements that interact to shape the teacher’s identity in the context of constant change and school reform. How do educational policies and their discourses shape these new teachers’ identities? How do these identities interact with reforms? Do these reforms match the identities of teachers or not? The importance of addressing these issues is greater when we consider that they may have an important impact—whether positive or negative—on the educational change processes.